User:Sam/jsMath

From WeBWorK
(Difference between revisions)
Jump to: navigation, search
Line 1: Line 1:
=== math ===
+
{|border=1 cellpadding=20
 
+
|<math>\int_a^x f(\alpha\,)\,dx</math>
* <math>\int_a^x f(\alpha\,)\,dx</math>
+
|<dmath>\int_a^x f(\alpha\,)\,dx</dmath>
* <math>\sqrt{\sqrt{\sqrt{x}}}</math>
+
|-
* <math>\left( \begin{smallmatrix} a&b \\ c&d \end{smallmatrix} \right)</math>
+
|<math>\sqrt{\sqrt{\sqrt{x}}}</math>
 
+
|<dmath>\sqrt{\sqrt{\sqrt{x}}}</dmath>
=== dmath ===
+
|-
 
+
|<math>\left( \begin{smallmatrix} a&b \\ c&d \end{smallmatrix} \right)</math>
* <dmath>\sqrt{x^2+2x+1}=|x+1| - \left(\left(\frac{2x^2}{x}\right)^2\right)^2</dmath>
+
|<dmath>\left( \begin{smallmatrix} a&b \\ c&d \end{smallmatrix} \right)</dmath>
* <dmath>\ E = \sum_{i=1}^N e^{- J_{ij} \sigma_i \sigma_j} </dmath>
+
|-
* <dmath>\therefore</dmath>
+
|<math>\sqrt{x^2+2x+1}=|x+1| - \left(\left(\frac{2x^2}{x}\right)^2\right)^2</math>
 +
|<dmath>\sqrt{x^2+2x+1}=|x+1| - \left(\left(\frac{2x^2}{x}\right)^2\right)^2</dmath>
 +
|-
 +
|<math>\ E = \sum_{i=1}^N e^{- J_{ij} \sigma_i \sigma_j} </math>
 +
|<dmath>\ E = \sum_{i=1}^N e^{- J_{ij} \sigma_i \sigma_j} </dmath>
 +
|-
 +
|<math>\therefore</math>
 +
|<dmath>\therefore</dmath>
 +
|}

Revision as of 19:05, 14 February 2008

\(\int_a^x f(\alpha\,)\,dx\) <dmath>\int_a^x f(\alpha\,)\,dx</dmath>
\(\sqrt{\sqrt{\sqrt{x}}}\) <dmath>\sqrt{\sqrt{\sqrt{x}}}</dmath>
\(\left( \begin{smallmatrix} a&b \\ c&d \end{smallmatrix} \right)\) <dmath>\left( \begin{smallmatrix} a&b \\ c&d \end{smallmatrix} \right)</dmath>
\(\sqrt{x^2+2x+1}=|x+1| - \left(\left(\frac{2x^2}{x}\right)^2\right)^2\) x+1| - \left(\left(\frac{2x^2}{x}\right)^2\right)^2</dmath>
\(\ E = \sum_{i=1}^N e^{- J_{ij} \sigma_i \sigma_j} \) <dmath>\ E = \sum_{i=1}^N e^{- J_{ij} \sigma_i \sigma_j} </dmath>
\(\therefore\) <dmath>\therefore</dmath>
follow us